Bubble slabs burned at 800 °C with different periods. Issue 1 (February 2021) - Al-Gasham, Thaar S.; Mhalhal, Jasim M.; Al-Magsusy, Lamea J.
Abstract: The bubble slabs are a modern type invented to reduce the self-weight significantly. However, limited studies were conducted on such slabs, and many influencing parameters still uninspected or need further investigations. The period of fire flame exposure is one of these factors. Hence, the current study was planned to examine bubble slabs' behavior when burned at 800 °C for different durations. Four bubble slabs were designed in analogous specifics. Three slabs were exposed to direct fire flame of 800 °C for three durations: 1, 1.5, and 2 hours. The remaining one was kept without exposure. Just the burning operations had accomplished, the slabs were statically tested under the influence of uniform loads. The results indicated that exposed slabs' failure mode changed to the shear mode, and the flexural cracks were limited. The slabs' strengths decreased owing to fire flame, where the residual strength of burned slabs were 50.24%-20.78% of that of the control slabs. Besides, essential decays in the mechanical characteristics of burned slabs were observed compared to the control one.